Single crystal X-ray structure of lawsone anion: evidence for coordination of alkali metal ions and formation of naphthosemiquinone radical in basic media - Salunke-Gawali, Sunita; Kathawate, Laxmi; Shinde, Yogesh; Puranik, Vedavati G.; Weyhermueller, Thomas (Journal of Molecular Structure, 2012)
2-hydroxy-1,4-naphthoquinone; Lawsone (Lw) is a natural compound found in henna leaves. The reaction of lawsone with `Na' metal (Lw-1), CH3COONa (Lw-2), NaOH (Lw-3), KOH (Lw-4), K2CO3 (Lw-5) and Tris(hydroxymethyl)aminomethane (Lw-6) were studied. Red orange solids obtained for Lw-1 to Lw-6 are characterized by Elemental Analysis, FTIR, (HNMR)-H-1 and EPR studies. The results reveal the coordination of alkali metals `Na' and `K' to lawsone anion. The single crystal X-ray structure of Lw-6 was solved and it crystallizes in triclinic space group P-1 with extensive hydrogen bonding network of C-H center dot center dot center dot O, N-H center dot center dot center dot O and O-H center dot center dot center dot O between cations and anions. Polycrystalline powder X-band EPR spectra of Lw-1 to Lw-5 shows signals similar to 2.004 at 133 K, while Lw-6 is EPR silent. The naphthosemiquinone (NSQ) radical formed in Lw-2 to Lw-5, is due to disproportion reaction of catechol and naphthoquinone. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: 2-Hydroxy-1; 4-naphthoquione; EPR; hydrogen bonding; Lawsone; Naphthosemiquinone radicals